2016
DOI: 10.2217/fmb-2015-0016
|View full text |Cite
|
Sign up to set email alerts
|

Propolis: A Potential Natural Product to Fight Candida Species Infections

Abstract: Propolis is an inhibitor of Candida virulence factors and represents an innovative alternative to fight candidiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
27
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 51 publications
4
27
0
5
Order By: Relevance
“…In this study, a greater reduction in C. albicans biofilm formation was observed at all concentrations compared to the biofilms produced by C. parapsilosis and C. tropicalis , and the reduction of biofilm in C. parapsilosis was significantly higher from the concentration of C. parapsilosis . 25 μg/mL and C. tropicalis at 250 μg/mL, corroborating the work of Tobaldini-Valerio et al (21) who also observed a greater biofilm reduction (~ 3.5 log) in C. albicans , followed by C. parapsilosis and C. tropicalis , with a reduction of approximately 2.8 and 2 log, respectively, at all Propolis Extract concentrations. tested.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, a greater reduction in C. albicans biofilm formation was observed at all concentrations compared to the biofilms produced by C. parapsilosis and C. tropicalis , and the reduction of biofilm in C. parapsilosis was significantly higher from the concentration of C. parapsilosis . 25 μg/mL and C. tropicalis at 250 μg/mL, corroborating the work of Tobaldini-Valerio et al (21) who also observed a greater biofilm reduction (~ 3.5 log) in C. albicans , followed by C. parapsilosis and C. tropicalis , with a reduction of approximately 2.8 and 2 log, respectively, at all Propolis Extract concentrations. tested.…”
Section: Discussionsupporting
confidence: 88%
“…Propolis is a resin that presents a number of medicinal properties [8], including anti-inflammatory activity, which could potentiate a possible antifungal topical action. Furthermore, the capacity of propolis to inhibit the biofilm formation of C. albicans has already been reported, along with the low cytotoxicity in human cells with the same PE used in the present study [15,26]. However, the antifungal property of PE has not yet been proved in biofilms formed by Fusarium species.…”
Section: Discussionmentioning
confidence: 55%
“…A possible limitation of this study was the absence of a comparison between the antibiofilm effects of propolis and conventional antifungals. However, it should be pointed out that other works carried out by our group [15,26] have shown propolis to be as or more efficient than other antifungal drugs. Moreover, Fusarium spp.…”
Section: Discussionmentioning
confidence: 84%
“…Tobaldini-Valerio et al [28] used the propolis extract against Candida species in both planktonic cells and biofilms, with the authors attributing the observed inhibitory activity to the flavonoids present in the extract. Phenolic compounds impair the growth and formation of C. albicans biofilms, possibly by suppressing genes responsible for adhesion and morphogenesis [29].…”
Section: Discussionmentioning
confidence: 99%